Climate change and forest genetic diversity: Implications for sustainable forest management in Europe - Koskela, Jaarko; Buck, A.; Teissier du Cros, E.; Bioversity International; European Forest Genetic Resources Programme (2007)
Climate change is increasingly recognized as one of the most important challenges faced globally by ecosystems and societies alike. According to the Intergovernmental Panel on Climate Change (IPCC), climate change could increase average temperatures by 2-4°C in Europe over the next 50 years and cause considerable changes in regional and seasonal patterns of precipitation. This will alter the environmental conditions to which forest trees in Europe are adapted and expose them to new pests and diseases. Climate change will thus create additional challenges for forest management, with consequent impacts on the economic and social benefits that societies and individuals derive from the forests, and on the biological diversity in forest ecosystems. Forest genetic resources in Europe are still facing several threats, including habitat destruction, fragmentation, pollution, poor silvicultural practices and use of low quality or poorly adapted forest reproductive material. The threats and the distribution of forest genetic resources do not respect national borders, and thus countries are dependent on each other's forest genetic resources for practising sustainable forest management. This interdependence of countries in terms of forest genetic resources is likely to increase in the future due to climate change. Because of the threats, the First Ministerial Conference on the Protection of Forests in Europe (MCPFE), held in Strasbourg in 1990, addressed the importance of conserving forest genetic resources (Strasbourg Resolution 2). This happened well before the United Nations Conference on Environment and Development (UNCED), organized in Rio de Janeiro in 1992, brought biodiversity into the global agenda. UNCED launched a new era in the international dialogue on forests and recognized, through the Convention on Biological Diversity (CBD), that countries have a sovereign right over their own genetic resources but also a responsibility to manage these resources sustainably.